ChemInform Abstract: Ni‐Catalyzed Borylation of Aryl Fluorides via C—F Cleavage. Issue 10 (February 2016) - Liu, Xiang‐Wei; Echavarren, Javier; Zarate, Cayetana; Martin, Ruben
Abstract: The scalable borylation of unactivated aryl fluorides using bis(neopentyl glycolato)diboron has a very broad substrate scope, thus tolerating sterically hindered compounds, nitrogen‐containing heterocycles as well as steroids, and multiple functional groups such as esters, amides, silyl ethers, acetals and pinacolates, but no nitriles, thioethers and chlorides.